2012
DOI: 10.1177/1090820x11430829
|View full text |Cite
|
Sign up to set email alerts
|

A Three-Dimensional Construct of the Aging Eyebrow: The Illusion of Volume Loss

Abstract: Although overall eyebrow volume does not change with age, the relative contribution of fat and soft tissue to the total volume does seem to change. This pattern also differs between males and females. As women age, the fat volume increases and the soft tissue volume decreases. In men, the shift from soft tissue volume to fat volume is less pronounced. Although many clinicians have been drawn to the concept of fat volume deflation as a key element of facial aging, this study does not support this perspective in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Patients with TED may be subject to the same volumetric deflation of the aging face, but the level of initial expansion is not age dependent. Papageorgiou et al, 15 examined eyebrow volume in 52 healthy individuals and, similar to this study, did not find eyebrow volume to change significantly with age at diagnosis. One could propose that the initial fat expansion in the brow during the transitional stages of TED may offer some buffer for regular age-related deflation changes.…”
Section: Discussionsupporting
confidence: 83%
“…Patients with TED may be subject to the same volumetric deflation of the aging face, but the level of initial expansion is not age dependent. Papageorgiou et al, 15 examined eyebrow volume in 52 healthy individuals and, similar to this study, did not find eyebrow volume to change significantly with age at diagnosis. One could propose that the initial fat expansion in the brow during the transitional stages of TED may offer some buffer for regular age-related deflation changes.…”
Section: Discussionsupporting
confidence: 83%
“…Computed tomographic scans are used for three-dimensional reconstruction, and the bone and soft-tissue volumetry often shows good results. 25,33,34 The isolation of muscle tissue by the difference in tissue density prevents manual selection and variations caused by human error. In the present study, the muscle showed atrophy when submitted to the surgical procedure for the insertion of implants; however, the chart showed an upward curve 3 months after surgery (the time when the patient can exercise), revealing a tendency to recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Papageorgiou and colleagues obtained similar results from their study on the 3D volumetric analysis of galeal and brow fat. 4 In their study, men showed a tendency toward fat enlargement with age. However, there was no change in overall thickness with age.…”
Section: Discussionmentioning
confidence: 89%
“…2,3 However, recently, a threedimensional (3D) volumetric analysis of eyebrow soft tissue revealed that fat volume increased with aging. 4 Hence, this study did not accept the common concept of lipoatrophy as a key element of facial aging.…”
Section: Introductionmentioning
confidence: 83%